Konsep, Batas-Batas, dan Jalur Pendidikan Islam - Ansori; Fariz Ramadan; Arawan; Kasful Anwar (PT. Hasba Edukasi Mandiri, 2025)
This article discusses the concept, boundaries, and paths of Islamic education as a fundamental framework in efforts to develop a complete Muslim individual. Islamic education is not only interpreted as a process of transferring knowledge, but also as character formation based on religious values. The concept of Islamic education includes efforts to foster faith, increase knowledge, and form noble morals. The boundaries of Islamic education include dimensions of space and time, starting from family, school, to society, and last a lifetime. Meanwhile, the path of Islamic education includes formal, non-formal, and informal paths that complement each other in achieving holistic educational goals. By understanding these three aspects, it is hoped that Islamic education will be able to answer the challenges of the times without losing its essence as a shaper of perfect human beings.